Investigation of FGFR2-IIIC Signaling via FGF-2 Ligand for Advancing GCT Stromal Cell Differentiation - Singh, Shalini (Public Library of Science, 2012)
Giant cell tumor of bone (GCT) is an aggressive bone tumor consisting of multinucleated osteoclast-like giant cells and proliferating osteoblast-like stromal cells. The signaling mechanism involved in GCT stromal cell osteoblastic differentiation is not fully understood. Previous work in our lab reported that GCT stromal cells express high levels of TWIST1, a master transcription factor in skeletal development, which in turn down-regulates Runx2 expression and prevents terminal osteoblastic differentiation in these cells. The purpose of this study was to determine the upstream regulation of TWIST1 in GCT cells. Using GCT stromal cells obtained from patient specimens, we demonstrated that fibroblast growth factor receptor (FGFR)-2 signaling plays an essential role in bone development and promotes differentiation of immature osteoblastic cells. Fibroblast growth factor (FGF)-2 stimulates FGFR-2 expression, resulting in decreased TWIST1 expression and increased Runx2, alkaline phosphastase (ALP) and osteopontin (OPN) expression. Inhibition of FGFR-2 through siRNA decreased the expression of ALP, Runx2 and OPN in GCT stromal cells. Our study also confirmed that FGF-2 ligand activates downstream ERK1/2 signaling and pharmacological inhibition of the ERK1/2 signaling pathway suppresses FGF-2 stimulated osteogenic differentiation in these cells. Our results indicate a significant role of FGFR-2 signaling in osteoblastic differentiation in GCT stromal cells.